Luteinized Ovarian Thecoma in a Postmenopausal Women Presenting with Virilization - Athula Kaluarachchi; Jeevan P. Marasinghe; Thuwan M. Batcha; Preethika Agunawela (Obstetrics and Gynecology International, 2009)
We report a case of luteinizing thecoma in a 58-year-old postmenopausal woman who presented with progressive androgenic features and hypertension of one year duration. She did not notice a significant change in her body weight or appetite. Her total serum testosterone level was 4.5 ng/mL. Ultrasound scan revealed a normal-sized uterus and a right-sided solid ovarian mass of 5 cm × 5 cm. Left ovary was normal. She had a total abdominal hysterectomy, bilateral salpingo-oophorectomy, and an omentectomy performed. Histological examination confirmed the diagnosis of luteinized thecoma. This case illustrates the necessity to consider the rare possibility of luteinized ovarian thecoma as a cause for virilization in a menopausal woman.